Atmospheric humidity affects global variation of bat echolocation via indirect effects - Kotila, Miika; Helle, Samuli; Lehto, Harry J.; Rojas, Danny; Vesterinen, Eero J.; Lilley, Thomas M. (Frontiers in Ecology and Evolution, 2022)
The peak frequency of bat echolocation is a species-specific functional trait linked to foraging ecology. It is tailored via evolution to suit conditions within the distribution range of each species, but the evolutionary drivers are not yet well understood. Global patterns of humidity correlate with many aspects of bat ecology. We hypothesized whether atmospheric absolute humidity could explain global peak frequency variation directly and indirectly via by increasing species’ body size and bat species richness. These hypotheses were tested using Bayesian phylogenetic path analysis on 226 tropical and subtropical bat species. In line with our predictions, we found a positive total effect of humidity on peak frequency, which was dominated by the positive indirect effects via body size and bat species richness. We did not observe the negative direct effect of humidity on peak frequency, which was hypothesized based on atmospheric attenuation of sound. In line with our expectations, excluding the predominantly clutter foraging bat families from our dataset downplayed the importance of the richness-mediated route. To conclude, our findings suggest that indirect effects, owing to ecology and biogeography of bat taxa, play major role in the global relationship between peak frequency and atmospheric humidity.